2013
DOI: 10.1038/ijir.2013.2
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dysfunction assessment and hormonal correlations in patients with polycystic ovary syndrome

Abstract: In this controlled study, we aimed to evaluate the sexual dysfunction of patients with polycystic ovary syndrome (PCOS) in comparison to healthy controls. We enrolled 64 sexually active women in our study. The PCOS group consisted of 32 women who met the Rotterdam diagnostic criteria, and the control group was composed of 32 age-matched, healthy females. In addition to the demographic and clinical characteristics of the participants, the hormonal and biochemical parameters were also studied. All patients were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
52
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 60 publications
3
52
0
1
Order By: Relevance
“…In light of this new knowledge, it is not surprising that there has been an increased awareness of female sexual dysfunction and the development of novel approaches to treatment. Numerous studies have demonstrated that infertile couples have significantly higher rates of sexual dysfunction than healthy controls 6, 9, 10, 11, 12. Similarly, it has been established that those with secondary infertility have more sexual dysfunction compared with those with primary infertility 10, 12.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In light of this new knowledge, it is not surprising that there has been an increased awareness of female sexual dysfunction and the development of novel approaches to treatment. Numerous studies have demonstrated that infertile couples have significantly higher rates of sexual dysfunction than healthy controls 6, 9, 10, 11, 12. Similarly, it has been established that those with secondary infertility have more sexual dysfunction compared with those with primary infertility 10, 12.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have demonstrated that infertile couples have significantly higher rates of sexual dysfunction than healthy controls 6, 9, 10, 11, 12. Similarly, it has been established that those with secondary infertility have more sexual dysfunction compared with those with primary infertility 10, 12. To date, however, no studies have stratified the sexual impact of infertility by demographic or clinical characteristics, including infertility etiology.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is accompanied with many gastrointestinal and cardiovascular side effects [4,5]. Recently emerging misoprostol, which is a synthetic derivative of PGE 1 , has been used as a drug for duodenal ulcer, but is extended to be used in obstetric fi eld, such as induction of labor and abortion, because it induces cervical dilatation and uterine contraction [6,7]. In addition, it is inexpensive and storable at room temperature, and causes fewer side effects [6,7].…”
mentioning
confidence: 99%
“…Recently emerging misoprostol, which is a synthetic derivative of PGE 1 , has been used as a drug for duodenal ulcer, but is extended to be used in obstetric fi eld, such as induction of labor and abortion, because it induces cervical dilatation and uterine contraction [6,7]. In addition, it is inexpensive and storable at room temperature, and causes fewer side effects [6,7]. Much research has been carried out to defi ne the most effective and best tolerated dosage and route of administration, but previous studies have reported its success rate mostly within 24 hours [8,9].…”
mentioning
confidence: 99%
“…A condição emocional destas mulheres, marcada pela ansiedade e depressão, podem impactar negativamente a função sexual delas (JONES et al, 2011) e rebaixamento da autoestima afetando a cumplicidade do casal (DROSDZOL e SKRZYPULEC, 2009). Há evidências de que a infertilidade pode ser agravada pelo aumento da obesidade e que essa está associada à depressão e por sua vez estaria associada à irregularidade menstrual sendo assim fator de risco para disfunção sexual (KOCELAK et al, 2012;ERCAN et al, 2013;ZUEFF et al, 2015).…”
Section: Introductionunclassified